HYBRID COAL: EFFECTS ON FEED/FUEL RATIO AND FUEL FEEDING METHOD IN LOW RANK COAL AND BIOMASS WASTE CO-PYROLYSIS PROCESS ON THE PRODUCTâS YIELD IN SEMI-DOUBLE CHAMBER REACTOR - Choirun Az Zahra, Aghietyas
HYBRID COAL: EFFECTS ON FEED/FUEL RATIO AND FUEL FEEDING METHOD IN LOW RANK COAL AND BIOMASS WASTE CO-PYROLYSIS PROCESS ON THE PRODUCT’S YIELD IN SEMI-DOUBLE CHAMBER REACTOR By Aghietyas Choirun Az Zahra NIM: 23018005 (Master’s Program in Chemical Engineering) Coal is a solid fossil fuel. Coal has a heating value that can be used as energy. From the time it was discovered in 200-300 million years ago, coal utilization still continues. Even so, there is a major problem with the use of coal, that is the pollution that released, where one of the biggest pollution is carbon dioxide which is one of the greenhouse gases. Carbon dioxide emission can be reduced by combining coal and biomass using co-pyrolysis, a process of decomposition of organic matter thermally without or using a limited amount using more than one fuels combined together. Biomass is known as a fuel that is more environmentally friendly because it has a zero or neutral carbon footprint. Combining coal and biomass will decrease the carbon footprint value compared to the use of coal alone. In consideration within that issue, this research was carried out regarding the manufacture of hybrid coal, a product of coal and biomass pyrolysis. The purpose of this study is to analyze the energy supply in the pyrolysis reactor to make hybrid coal, with the specific aim being to find the ratio of fuel vs mixture of coal and biomass used for feed that needed for the production of hybrid coal in semi-double chamber reactors with the batch or semibatch type of operation and to calculate the carbon footprint of the manufacture of hybrid coal in the production process. The reactor operated atmospherically, and the feed mixture of coal and biomass was fixed, which is 250 grams. There are two chambers in the reactor, the combustion chamber and the pyrolysis chamber. The combustion chamber was used for the heat supply for co-pyrolysis using heat from biomass combustion. Co-pyrolysis was carried out under minimal oxygen conditions. There were two process variables varied, the variable feed:fuel ratio and fuel feeding method. Feed:fuel ratio is varied by 1:3, 1:4 and 1:5, while the fuel feeding method is varied by one time feeding and two times fuel feeding. The coal used was subbituminous C coal obtained from the Center for Research and Development of Mineral and Coal Technology (TekMIRA Research Center) and biomass for co-pyrolysis was Mahogany sawdust waste, with a composition of biomass in the mixture was 30%. From the the study, it was found that the variation that produced the best energy yield was a variation of the feed: fuel ratio 1:3 in the one-time fuel feeding method. This variation succeeded in increasing the rank of coal to subbituminous class B. While the calculation of the iv carbon footprint from hybrid coal production to its utilization for fuel resulted in a decline of up to 20.89% comparing with utilization using coal only. The resulting hybrid coal is able to compete with its raw coal as a first step towards clean coal technology.